Genomic and transcriptomic insights into vertebrate host-specific Lactobacillus johnsonii adaptation in the gastrointestinal tract - Keerthikka Ravi; Nicole R. Falkowski; Gary B. Huffnagle (mSphere)
ABSTRACT We conducted a comparative genomic analysis of Lactobacillus johnsonii strains isolated from the gastrointestinal tract of diverse vertebrate hosts to explore the genetic basis of host specificity. We then utilized transcriptomics analysis to investigate the expression profile of identified rodent-specific genes in mouse isolate MR1 during in vitro and in vivo growth conditions. There was significant heterogeneity among strains, in both genome sequence and content, with phylogenetic clustering of strains into distinct clades associated with rodent or avian sources. There were not sufficient genomes to identify whether porcine isolates formed their own genetic clade. However, human isolates did not form a distinct clade. Functional enrichment analysis revealed significant enrichment of several genes, including surface proteins and accessory secretory pathway-related genes, as well as tyrosine decarboxylase genes in rodent isolates compared to avian isolates, including in mouse isolate MR1. A total of 40 genes were identified as rodent-associated, and all were transcriptionally active in L. johnsonii MR1. The global transcriptomic analysis of L. johnsonii MR1 was done using cells grown anaerobically, at 37˚C, under both the late-exponential phase and stationary phase, as well as during in vivo growth in the cecum of mono-colonized germ-free mice. Several of these genes were uniquely regulated during late exponential vs stationary phase growth and in vivo colonization in mice, highlighting their potential role in nutrient adaptation and host-microbe interactions.IMPORTANCELactobacillus johnsonii is a well-known probiotic species with health-beneficial properties, including host immunomodulation and pathogen inhibition. Its growing relevance in the medical industry highlights the need to understand its biology, particularly how it adapts to different host environments. In bacteria, niche adaptation is often accompanied by the loss or gain of coding sequences along with changes in the genome size. In this study, we explored the genetic diversity of L. johnsonii strains from the gastrointestinal tracts of various vertebrates such as rodents, birds, swine, and humans. We found associations between genome content and host species of origin and could conceptually demonstrate that these genes are being differentially transcribed under varying conditions. Several functions were associated with specific host groups, suggesting that L. johnsonii strains have adapted to their hosts over time.